(untitled) (Journal of the College of Education for Women, 2022)
The study aimed at recognizing the availability of the cultural intelligence dimensions in social studies book at the high school in the kingdom of Saudi Arabia (curricula system- joint program). The study used the descriptive approach and content analysis method. As tools of the study, the study adopted a list of cultural list of indicators and dimensions that suits the secondary stage social curricula. It further adopted a content analysis form designed to analyze the social studies book in the secondary school in the kingdom of Saudi Arabia. The study has reached several results, the most significant results were: There is a difference in including the cultural intelligence dimensions in social studies book at high school in the kingdom of Saudi Arabia (curricula system- joint program). The cognitive dimension is the most included dimension with a frequency of 2497, representing 14%. However, the motivational dimension is the second with a 1019 frequency that represents 29.99%. The third and the last is the behavioral dimension with a 259 frequency, i.e., 6.86%. The results of the study have illustrated the existence of a disparity between the book units in incorporating the cultural intelligence dimensions. This is because the second unit has come first with a frequency of 845 (i.e., 22.38%) while the forth unit was the sixth and the last with a 516 frequency (i.e., 13.66%).